ANALISIS MATERI SULIT DIPAHAMI DAN MISKONSEPSI MAHASISWA DALAM MATA KULIAH KALKULUS INTEGRAL - Dona Fitriawan; Romal Ijuddin; Silvia Sayu (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2022)
This study aims to analyze and describe what materials are difficult in calculus courses and also materials that are misconceptions. This research was conducted to improve the competence of students in the future. The formulation of the problem in this study is